Governance and Conflict Management in Public Services Post-Bureaucratic Reform - Abdul Wakhid, Ali; Qohar, Abd.; Faizal, Liky (JURNAL TAPIS, 2023)
Handling and Governance of complaints in public services after bureaucratic reform is one of the efforts made to create a clean and efficient government. This is intended to improve welfare and create justice and certainty in meeting the needs of the community as citizens. For the sake of the continuity of public service delivery and protecting the rights of citizens from possible abuses in public service practices, it is necessary to manage complaints and conflicts that may arise between the community and the bureaucracy. This study aims to: aims to analyze the management of complaints and conflict management in public services after Law Number 25 of 2009 concerning Public Services. Research is a doctrinal/normative research. This study analyzes the management of complaints and conflicts that may arise between the community and the bureaucracy. Research Results are To ensure the implementation of public services properly and protect the rights of every citizen from possible violations or abuses in the implementation of public services, regulations have been made for the management of complaints, disputes, and disputes that may arise between the community of service users and public service providers in the Law on Public Services.